2020
DOI: 10.3390/vaccines8010059
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of A Baculovirus-Expressed VP2 Subunit Vaccine for the Protection of White-Tailed Deer (Odocoileus virginianus) from Epizootic Hemorrhagic Disease

Abstract: Epizootic hemorrhagic disease virus (EHDV) is an arthropod-transmitted RNA virus and the causative agent of epizootic hemorrhagic disease (EHD) in wild and domestic ruminants. In North America, white-tailed deer (WTD) experience the highest EHD-related morbidity and mortality, although clinical disease is reported in cattle during severe epizootics. No commercially licensed EHDV vaccine is available in North America. The objective of this study was to develop and evaluate a subunit vaccine candidate to control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…These findings were consistent with previous studies in which cattle experimentally infected with EHDV-6 developed no, or very mild, clinical signs [77,78]. Cattle vaccinated with the recombinant VP2 proteins of EHDV-2 and EHDV-6 produced virus-neutralizing antibodies against their homologous virus serotypes; the ability to neutralize heterologous viruses was limited [73]. A recent cattle challenge study, designed to generate a panel of bovine reference sera, provided data regarding the presence and absence of cross-neutralization between serotypes [79].…”
Section: Cattle In Vivo Studiessupporting
confidence: 92%
See 2 more Smart Citations
“…These findings were consistent with previous studies in which cattle experimentally infected with EHDV-6 developed no, or very mild, clinical signs [77,78]. Cattle vaccinated with the recombinant VP2 proteins of EHDV-2 and EHDV-6 produced virus-neutralizing antibodies against their homologous virus serotypes; the ability to neutralize heterologous viruses was limited [73]. A recent cattle challenge study, designed to generate a panel of bovine reference sera, provided data regarding the presence and absence of cross-neutralization between serotypes [79].…”
Section: Cattle In Vivo Studiessupporting
confidence: 92%
“…A recently developed WTD fawn challenge model addressed the question of whether such maternallyderived antibodies against EHDV are protective against challenge; in this study it was demonstrated that even low titers of maternal antibodies to EHDV-2 provided protection against clinical disease and greatly reduced levels of viremia following challenge with the homologous EHDV-2 serotype virus [72]. Finally, the WTD model was recently applied to vaccine discovery, enabling the evaluation of immunogenicity and efficacy induced by a novel subunit vaccine candidate comprised of the recombinant viral capsid VP2 protein of EHDV-2 [73]. This vaccine, which was efficacious in protecting WTD from viremia and clinical disease following an experimental challenge with a virulent EHDV-2 virus, has additional benefits including potential Differentiating Infected from Vaccinated Animals (DIVA) compatibility and wider safety margins than live-attenuated vaccines.…”
Section: Wtd In Vivo Studiesmentioning
confidence: 88%
See 1 more Smart Citation
“…Five of the six deer were pregnant; the number of fetuses per deer are indicated in Table 1. Four naïve white-tailed deer from a previous study evaluating a baculovirus-expressed subunit vaccine for the protection from epizootic hemorrhagic disease (EHD), performed in 2017 9 , were used as controls (Table 1 and Figure 1).…”
Section: Virus Challenge Of Animalsmentioning
confidence: 99%
“…With its considerable animal health and economic impact, bluetongue disease is a World Organization for Animal Health (OIE)-reportable disease [ 19 , 22 ]. Control methods for BTV include limited vaccines [ 23 , 24 , 25 , 26 ], livestock management [ 27 , 28 ], and vector control [ 29 ], with EHDV control often emulating standards set by BTV research [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%